1998
DOI: 10.1093/brain/121.11.2083
|View full text |Cite
|
Sign up to set email alerts
|

Prospective and retrospective studies of recovery in aphasia. Changes in cerebral blood flow and language functions

Abstract: Prospective and retrospective language evaluations and single photon emission computed tomography (SPECT) scans were performed in order to study the relationship between post-stroke recovery from aphasia and changes in cerebral blood flow (CBF) in groups of patients who had made a good recovery and those who had not. For the prospective study, 20 right-handed patients with aphasia secondary to an acute cerebrovascular accident (CVA) in the left middle cerebral artery territory received language evaluations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
62
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(67 citation statements)
references
References 36 publications
5
62
0
Order By: Relevance
“…Some case studies have also related the right hemisphere to language recovery (e.g., Cummings, Benson, Walsh, & Levine, 1979). Furthermore, more recent clinical studies have emphasized the role of the right hemisphere in spontaneous recovery of language (Thulborn, Carpenter, & Just, 1999;Mimura et al, 1998;Weekes, Coltheart, & Gordon, 1997;Ohyama et al, 1996;Weiller et al, 1995;Papanicolaou, Moore, Deutsch, Levin, & Eisenberg, 1988). Imaging results have shown shifts of activity to right hemisphere areas homotopic to the classical left hemisphere language areas (Ohyama et al, 1996;Weiller et al, 1995), overall stronger activity in the right than in the left hemisphere (Cao, Vikingstad, George, Johnson, & Welsch, 1999;Papanicolaou et al, 1988), or pronounced increase of right hemisphere activity during recovery (Thulborn et al, 1999).…”
Section: Role Of Right Hemisphere In Aphasia Recovery and Rehabilitationmentioning
confidence: 99%
“…Some case studies have also related the right hemisphere to language recovery (e.g., Cummings, Benson, Walsh, & Levine, 1979). Furthermore, more recent clinical studies have emphasized the role of the right hemisphere in spontaneous recovery of language (Thulborn, Carpenter, & Just, 1999;Mimura et al, 1998;Weekes, Coltheart, & Gordon, 1997;Ohyama et al, 1996;Weiller et al, 1995;Papanicolaou, Moore, Deutsch, Levin, & Eisenberg, 1988). Imaging results have shown shifts of activity to right hemisphere areas homotopic to the classical left hemisphere language areas (Ohyama et al, 1996;Weiller et al, 1995), overall stronger activity in the right than in the left hemisphere (Cao, Vikingstad, George, Johnson, & Welsch, 1999;Papanicolaou et al, 1988), or pronounced increase of right hemisphere activity during recovery (Thulborn et al, 1999).…”
Section: Role Of Right Hemisphere In Aphasia Recovery and Rehabilitationmentioning
confidence: 99%
“…Some studies have suggested a LH role in better aphasia recovery (Metter 1987;Heiss et al, 1997;Karbe et al, 1998;Miura et al, 1999;Warburton et al, 1999). Many studies have suggested that both hemispheres are important, depending on the type of language behavior and when it was examined (Weiller et al, 1995;Belin et al, 1996;Basso et al, 1998;Mimura et al, 1998;Cao et al, 1999;Hund-Georgiadis et al, 1999;Gold & Kertesz, 2000;Ansaldo et al, 2002;Zahn et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…3,[14][15][16] Supplemental data at www.neurology.org Right hemisphere compensation has been attributed to homologous receptive and expressive regions. 9,[17][18][19][20] Some studies suggest a higher likelihood of interhemispheric reorganization with earlier onset and certain pathologic substrates. Nevertheless, the degree and location of activation in the right hemisphere is not well documented.…”
mentioning
confidence: 99%
“…We identified the point maxima for two areas implicated in language processing for this task: the MTG (BA 21; Ϫ52, Ϫ30, Ϫ8) and the left IFG (BA 44/45; Ϫ44, 30, 18). Homologous voxels were defined on the right side of the brain by reversing the sign of the x coordinate ([52, Ϫ30, Ϫ8] and [44, 30,18] for the two regions). Each participant's activated voxel with the closest individual distance to the group map voxel for each area was identified and mean distances were calculated.…”
mentioning
confidence: 99%